Improving management of glycaemic control in people with T2DM in primary care: estimation of the impact on the clinical complications and associated costs - Mata-Cases, M. (BMC Health Serv Res, 2020)
BACKGROUND: To estimate the potential benefits in terms of avoided complications and cost reduction if the Spanish health system would encourage the intensification of treatment for better glycaemic control in adults with Type 2 diabetes from the current HbA1c target used in clinical practice of 68 mmol/mol to a target of 53 mmol/mol. METHODS: The IQVIA Core Diabetes Model (version 9.0) was used to model the impact of these changes in respect of micro- and macrovascular complications and the associated costs. The modelling was based on data derived from the SIDIAP-Q population database from Catalonia, taking a random cohort of 10,000 people with type 2 diabetes and dividing it into sub-groups based on their baseline HbA1c. RESULTS: The CDM modelling showed that the average cost reduction per person varies depending on baseline HbA1c. The model estimates that after 25 years, people with a baseline HbA1c between 48 and 58 mmol/mol and > 75 mmol/mol show an average cost reduction of €6027 and €11,966, respectively. Applying the per-person cost reduction to the cohorts of the prevalent population in Spain (1,910,374) the overall estimated cost reduction was €14.7 billion over 25 years. The improvements in outcomes resulted in an estimated reduction of more than 1.2 million complications cumulatively over 25 years, of which more than 550,000 relate to diabetic foot and more than 170,000 related to renal disease. CONCLUSION: Over a 25 year period, Spain could considerably reduce costs and avoid major complications if, on a population level, more ambitious glycaemic control, according to Spanish or EU guidelines, could be achieved among people with type 2 diabetes by reducing the HbA1c threshold for treatment intensification. Although there is a slower trajectory for benefits in earlier years, there is a much more rapid benefit gain between years 5 and 15.